PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Sari, Tri Wulan; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of KAP size, industrial specialization, audit assignment period, client important, willingness reporting of audit opinion, firm size and leverage to the accrual earnings management. The population is all manufacturing companies which are listed in Indonesia Stock Exchange. The sample collection technique has been done by using purposive sampling so the samples which have been obtained are 314 firm years. The statistic method has been done by using multiple regressions analysis. The result of goodness of fit/F test has obtained significant value 0.036 < 0.05 (level of significant) which indicates that all variables in the research model can explain the changes of earnings management or models which have been built have met the fit criteria. The determination coefficient test with its Adjusted R Square (Adjusted R2) is 0.123 or 12.3% it means that all independent variables can explain the dependent variable and the partial test. This research has been processed by using SPSS version 12. The result of partial test shows that there are three models which have significant influence to the earnings management i.e. KAP size, industrial specialization, and audit assignment period whereas client important variable, the willingness reporting of audit opinion, firm size and leverage do not have any significant influence to the earnings management.Keywords: Audit Quality, Firm Size, Leverage, Earnings Management